Pelatihan Higiene dan Sanitasi Makanan pada Pedagang Makanan di Kantin Sekolah Dasar - Jamilatur Rohmah; Siti Cholifah; Vanda Rezania (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2019)
The school canteen has an important role to fulfill the food needs of school children. The need for fulfillment of hygienic foods is ordered by the factors of place and hygiene of the food handlers. Foods that do not meet the requirements and safety that can be given due to health problems or diseases related to food such as diarrhea, cholera, dysentery, typhus, and other food poisoning. The number of food handlers in the cafeteria of SD Muhammadiyah 1 and 2 Sidoarjo competes 6 people. Based on the results of observations and interviews, they did not have sufficient educational background and never gained knowledge about food hygiene and sanitation. The purpose of this PPM activity are to improve the knowledge, attitudes, and behavior of food handlers about food hygiene and sanitation so not to harm their consumers health, especially school children. The method used is a training and mentoring model for food handlers starting when preparing food, processing, and serving to customers. The results of these program can be known about changes in the knowledge and skills of food handlers in food hygiene and sanitation.